ANALISIS PERAN DINAS SOSIAL KOTA DALAM PEMBINAAN GELANDANGAN DAN PENGEMIS DI KOTA BENGKULU - Ameliyah, Ulva; Tarigan, Jarto; Nursanty, Nursanty (JURNAL ILMIAH EDUNOMIKA, 2024)
This thesis entitled "Analysis of the Role of Social Service fostering homeless and beggars in the city of Bengkulu". One of the problems with the onset of bums and beggars coaching is not optimal implementation of coaching is done by the Department of Social city in accordance with the duties and functions of the Department. Coaching is done by the Social Service conducted by the city of Bengkulu: Bengkulu Mayor Regulation Number 26 of 2008, Regulation No. 03 of 2008 on Public Peace and Order In the region of Bengkulu. The purpose of this study was to determine how the Role of Social Service in coaching vagrants and beggars in the city of Bengkulu. This type of research is descriptive qualitative research, the data is taken from sources which are determined based on purposive sampling technique. The data collection was done by using in-depth interviews, observation and document study. The results showed that the role of Social Service in fostering homeless and beggars in the city of Bengkulu has aligned with implementation instructions. But still need to make improvements and reform in order to create a better coaching. To the authors suggested that take concrete steps in terms of coaching is done on the homeless and beggars in the city of Bengkulu is conducted on an ongoing basis and communicate with the relevant agencies.